Analyzing Learners' Perceptions of ChatGPT - Assisted English Language Learning - Nur Hasanah; Intan Wijayanti (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2026)
This research endeavors to systematically analyses the perceptions of language learners concerning the integration of ChatGPT as an innovative tool for augmenting their English language competencies. Adopting a qualitative paradigm through a case study design, the study meticulously selected participants based on rigorous inclusion criteria, namely, documented experience employing ChatGPT not only for university assignment but also potentially for extracurricular or personal endeavors. Specifically, four undergraduate students of the Early Childhood Education Program, Faculty of Tarbiyah and Teacher Training at the second semester, enrolled in UIN Kiai Ageng Muhammad Besari Ponorogo deliberately chosen to participate, ensuring a focused yet representative sample within this contextual framework. The empirical findings robustly substantiate learners’ affirmative perceptions of ChatGPT’s instrumental value in fostering English language skill enhancement. Participants consistently emphasized its multifaceted utility across key domains, including interactive speaking exercises to improve fluency, enhanced writing skills, quick text translation to aid comprehension, vocabulary expansion, and mastery of idiomatic expressions, as well as assistance with grammatical corrections. From a broader perspective, the predominantly positive appraisals of ChatGPT’s applicability signal compelling opportunities for educational stakeholders. Higher education institutions and digital language learning platform are encouraged to strategically embed analogous AI-powered conversational tools into curricula and resources.